Interventions to reduce anxiety among college students In Indonesia: A scoping review - Hadi Abdillah; Laili Rahayuwati; Iyus Yosep (Jurnal Keperawatan Padjadjaran, 2026)
Background: Anxiety among college students is a growing mental health concern, particularly in Indonesia, where students face academic pressure, challenges related to academic major selection, performance demands, transition to adulthood, and career uncertainty. These stressors are compounded by limited access to formal psychological services, mental health stigma, and financial barriers, resulting in a substantial treatment gap. Purpose: To identify and map evidence-based interventions used to reduce anxiety and psychological distress among college students in Indonesia across various academic majors and fields of study. Methods: This scoping review followed the Population–Concept–Context (PCC) framework. Relevant studies were identified through PubMed, Scopus, CINAHL, and Google Scholar using keywords related to intervention, anxiety, college students, and Indonesia. Studies were included if they involved college student populations, examined interventions targeting anxiety or psychological distress, and were published in Indonesian or English. Results: The database search yielded 269 reports. After title, abstract, and full-text screening, 15 studies met the inclusion criteria and were included in the final analysis. Five key themes emerged: (1) a predominant focus on academic-related anxiety; (2) dominance of Cognitive Behavioral Therapy (CBT), Acceptance and Commitment Therapy (ACT), and mindfulness-based interventions; (3) benefits of brief relaxation, art-based, and expressive approaches; (4) feasibility of digital, counselor-guided, and culturally adapted programs, including Self-Help Plus; and (5) the use of efficient, mostly quasi-experimental designs with short intervention durations. Overall, the interventions demonstrated reductions in anxiety and psychological distress among college students. Conclusion: Reducing anxiety among college students in Indonesia requires a multimodal and holistic approach that integrates evidence-based psychological therapies with culturally responsive and accessible strategies. The growing use of brief, digital, and culturally adapted interventions offers a promising pathway to address mental health service gaps in Indonesian higher education.